2020
DOI: 10.1101/2020.11.09.375329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of XPB/Ssl2 dsDNA translocation processivity in transcription-start-site scanning

Abstract: The general transcription factor TFIIH contains three ATP-dependent catalytic activities. TFIIH functions in nucleotide excision repair primarily as a DNA helicase and in Pol II transcription initiation as a dsDNA translocase and protein kinase. During initiation, the XPB/Ssl2 subunit of TFIIH couples ATP hydrolysis to dsDNA translocation facilitating promoter opening and the kinase module phosphorylates the C-terminal domain to facilitate the transition to elongation. These functions are conserved between met… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Optical tweezer experiments are consistent with TFIIH within the PIC having median processivity on the order of ~90 basepairs, consistent with the average distance of TSSs downstream of yeast TATA boxes. However, purified holo-TFIIH from yeast has much reduced measured processivity and human TFIIH has essentially none 14 . Given that TFIIH activity is predicted to be altered extensively by cofactor interactions in both transcription and nucleotide excision repair (NER), it will be important to understand TFIIH functions within the PIC in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical tweezer experiments are consistent with TFIIH within the PIC having median processivity on the order of ~90 basepairs, consistent with the average distance of TSSs downstream of yeast TATA boxes. However, purified holo-TFIIH from yeast has much reduced measured processivity and human TFIIH has essentially none 14 . Given that TFIIH activity is predicted to be altered extensively by cofactor interactions in both transcription and nucleotide excision repair (NER), it will be important to understand TFIIH functions within the PIC in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous lines of evidence suggest TSS selection by S. cerevisiae Pol II involves a unidirectional scanning mechanism in which the preinitiation complex (PIC) assembles at an upstream core promoter and interrogates consecutive downstream positions for usable TSSs [9][10][11][12][13] . TFIIH is proposed to drive Pol II scanning through ATP-dependent DNA translocase activity 12,[14][15][16][17] . An opticaltweezer-based single molecule analysis of reconstituted S. cerevisiae PICs indicated that an ATP/dATP-induced activity within the PIC causes shortening of the distance between upstream and downstream DNA 17 .…”
Section: Introductionmentioning
confidence: 99%